Fast beam monitor diamond‐based devices for VUV and X‐ray synchrotron radiation applications. (13th February 2019) - Di Fraia, Michele; De Sio, Antonio; Antonelli, Matias; Nesti, Renzo; Panella, Dario; Menk, Ralf H.; Cautero, Giuseppe; Coreno, Marcello; Catone, Daniele; Zema, Nicola; Callegari, Carlo; Pace, Emanuele
Abstract : Results of an extensive measurement campaign aiming at exploiting the capabilities of a custom‐built diamond‐based device to monitor the time structures of VUV and X‐ray synchrotron radiation light with sub‐100 ps timescale are presented. Abstract : The improved performance of third‐generation light sources and the advent of next‐generation synchrotron radiation facilities require the use of extremely precise monitoring of the main photon‐beam parameters, such as position, absolute and relative intensity, and temporal structure. These parameters, and associated real‐time feedbacks, are fundamental at the beamline control level and at the machine control level, to improve the stability of the photon beams and to provide bunch‐to‐bunch quantitative information. Fast response time, high radiation hardness and visible–blind response are main features of photon‐beam monitors for VUV and X‐ray synchrotron radiation beamlines; hence diamond‐based detectors are outstanding candidates. Here, results are presented of an extensive measurement campaign aiming at optimizing the capabilities of diamond detectors to discern time structures below the 100 ps timescale. A custom‐built device has been fabricated and tested at the Italian Synchrotron Radiation Laboratory Elettra in Trieste. The results obtained show that diamond is an excellent material for ultra‐fast photon pulses with picosecond time resolution; finally the possibilities for application at free‐electron laser sources are discussed.